Detection, diagnosis, Koch's postulate, hepatorenal and antioxidant indicators for some systemic pathogenic fungi invading the liver and kidneys of African catfish (Clarias gariepinus) in Egypt with a histopathological approach. (18th February 2022) - Mahboub, Heba H.; Nada, Hend S.; Abdel‐Ghany, Heba M.; Ghanem, Rania; Ahmed Ismail, Tamer; Abdel Rahman, Afaf N.
Abstract: Recently, systemic fungal infections have emerged as significant causes of fish morbidity and mortality. Hence, the current study investigates the occurrence of some pathogenic systemic fungi inducing severe lesions in the liver and kidneys of African catfish. Two hundred diseased African catfish were collected from private fish farms in Egypt, and only 120 fish were infected with 212 different fungal isolates at a rate of 60%. The seasonal survey revealed isolation of 72 isolates of yeast ( Candida albicans ) and 140 isolates of moulds including non‐pigmented moulds, Aspergillus ochraceous and Aspergillus flavus, as well as pigmented mould ( Cladosporium herbarum ). The isolated fungi induced characteristic post‐mortem lesions. To date, this is the first report for isolation of C . herbarum and C . parapsilosis from Nile catfish liver and kidneys. Various techniques were performed to identify the fungi including gross observation, microscopic examination of tissue squashes, in vitro culture and histopathology. Koch's postulate was fulfilled to confirm the fungal pathogenicity. The challenged fungi altered the hepatorenal indicators (ALP, AST, ALT, urea and creatinine) and oxidative stress biomarkers (MDA, CAT and SOD). The results indicate the virulence of the isolated fungi, and future studies are needed for treatment trials.